CD38-Induced Apoptosis and Mitochondrial Damage is Restored by Nicotinamide in Prostate Cancer - Kanayama, Mayuko; Luo, Jun (Frontiers in Molecular Biosciences, 2022)
Nicotinamide adenine dinucleotide (NAD+) is an essential molecule for living organisms. CD38 is a key NAD+-dependent enzyme which breaks down NAD+ to cyclic ADP-ribose (ADPR) and nicotinamide (NAM, vitamin B3), and NAM can be recycled to synthesize NAD+. CD38 expression is consistently silenced by methylation in prostate cancer and progressively downregulated in advanced castration-resistant prostate cancer, suggesting a connection between NAD+ and prostate carcinogenesis as well as prostate cancer progression. However, the functional interplay between NAD+, CD38, and NAM remains largely uncharacterized in prostate cancer cells. In this study, we generated stable LNCaP95 cell clones expressing varying levels of CD38 upon induction by doxycycline. We demonstrate that CD38 overexpression resulted in apoptosis accompanied by cleavage of poly (ADP-ribose) polymerase 1 (PARP1). CD38 overexpression also dramatically reduced intracellular NAD+ levels and decreased mitochondrial respiration as measured by oxygen consumption rate. We further show that some but not all of these CD38-induced phenotypes could be rescued by exogenous NAM. Treatment of cells with NAM rescued CD38-induced apoptosis and mitochondrial stress but did not restore intracellular NAD+ levels. We also found that NAM demonstrated biphasic effect on mitochondria function, a finding that can be explained by the dual role of NAM as both a precursor of NAD+ and also as a suppressor of a number of NAD+-dependent enzymes. Collectively, these findings provide additional insight supporting the functional relevance of CD38 loss in prostate cancer by linking cell-autonomous regulation of mitochondrial function and prostate cancer.